2012
DOI: 10.4103/0970-9185.92442
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for cancellation of operation on the day of intended surgery in a multidisciplinary 500 bedded hospital

Abstract: Background:Cancellation of operations in hospitals is a significant problem with far reaching consequences. This study was planned to evaluate reasons for cancellation of elective surgical operation on the day of surgery in a 500 bedded Government hospital.Materials and Methods:The medical records of all the patients, from December 2009 to November 2010, who had their operations cancelled on the day of surgery in all surgical units of the hospital, were audited prospectively. The number of operation cancelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
1
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 9 publications
7
117
1
12
Order By: Relevance
“…This assumption is based on two premises: (a) most reasons (80%) for surgical cancellations are avoidable, including clinical reasons, such as uncontrolled systemic arterial hypertension or diabetes mellitus on the day of surgery (26) . These alterations are considered the main reasons for surgery cancellations (22,26) ; (b) out of 6.79% of elective surgeries canceled in the institution under study, 3.13% occurred for "non-clinical reasons" and 3.26% for "clinical reasons". Furthermore, the main reasons for surgical cancellations at the institution under study are not different from those found in hospital services in developed countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is based on two premises: (a) most reasons (80%) for surgical cancellations are avoidable, including clinical reasons, such as uncontrolled systemic arterial hypertension or diabetes mellitus on the day of surgery (26) . These alterations are considered the main reasons for surgery cancellations (22,26) ; (b) out of 6.79% of elective surgeries canceled in the institution under study, 3.13% occurred for "non-clinical reasons" and 3.26% for "clinical reasons". Furthermore, the main reasons for surgical cancellations at the institution under study are not different from those found in hospital services in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is the nurse's responsibility to use the information about the microeconomic features of the process, as well as direct and opportunity costs, in order to manage the SC and develop strategies to solve the problem (1) . Considering that: a) a low rate of surgical cancellations is one of the indications of quality and, consequently, of management efficiency and, therefore, cancelling surgeries implies in underuse of operating rooms and increase of the waiting list and institutional cost (22) ; b) the actors involved in the surgery itinerary, responsible for assistance or management, must be aware that the underuse of public structure raises the cost of the services, which will be reflected upon users, family members and themselves, not only financially but also psychologically; c) the misuse of public resources does not contribute to investments in working conditions and to the quality of the service offered to citizens;…”
Section: Introductionmentioning
confidence: 99%
“…General surgery had the highest number of cases scheduled for operation at 2 196 (30.1%) followed by orthopaedics at 1 812 (25%) in India. 23 The DOS cancellation rate according to specialty varied in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Cancellation for long preceding surgery was identified in 2.6% of cases. Kumar and Gandhi 13 in India reported 63% of cancellations being due to a lack of time related to a long preceding surgical operation. Late starting time, going beyond expected duration and a long time cleaning the OT between two cases led to a waste of resources.…”
Section: Acknowledgementmentioning
confidence: 99%